The low-frequency radiation and scattering of sound from bubbly mixtures near the sea surface - Carey, W; Roy, R (European Commission, 1995)
The radiation and scattering from micro-bubble clouds with volume fractions greater than .01% are described with a theoretical model and measured data. In the low frequency limit the radiation and scattering of sound was determined to be monopole in the free field. The natural frequency of the cloud is predicted by a modified Minnaert equation. The measured back scatter target strength was found to be consistent with theoretical expectations.